Daya Saing Daerah Tujuan Wisata (Studi Kasus Rendahnya Daya Saing Taman Wisata Alam Kawah Ijen Banyuwangi) - Riyadi, Slamet; Hadiwidjojo, Djumilah; .., Djumahir; Hakim, Luchman (Jurnal Aplikasi Manajemen, 2012)
Competition Level of Tourism Resort: A Case Study in Low Competition Level of Ijen Crater Tourism Resort in Banyuwangi. Doctorate Program in Management Science, Faculty of Economics and Business, University of Brawijaya. Promoter: Djumilah Hadiwidjojo; Co-Promoters: Djumahir and Luchman Hakim. This research aims at revealing and examining: (1) Low number of visitors and low competition level of Ijen Crater Tourism Resort in Banyuwangi; (2) Characteristic stagnancy of Ijen Crater Tourism Resort in Banyuwangi; (3) The best strategy to rise competition level of Ijen Crater Tourism Resort in Banyuwangi. The research is conducted in Ijen Crater Tourism Resort in Banyuwangi using Positivistic Approach. This research is designed to apply interpretative study case, particularly single case interpretative study case. Additionally, Milles'and Huberman's Interactive Model is used in the analysis. The prominent findings of this research are: (1) Ijen Crater Tourism Resort is beautiful and unique, but the number of visitors and its competition level are relatively low. The low number of visitors is due to its characteristic which belongs to special tourism destination which is only for those who love adventure. Moreover, the location is very difficult to reach. The low competition level is resulted from unsupportive influential factors; (2) Characteristic stagnancy of Ijen Crater Tourism Resort is triggered by managerial aspect, in which the communication between Department of Natural Resources Conservation or Balai Besar Konservasi Sumber Daya Alam (BBKSDA), as the management, and Indonesia Culture and Tourism Ministry is not effective; (3) Niche Marketing Strategy and Marketing Mix can be effectively used to rise the competition level; (4) Resource-Based View (RBV) is applied to determine competition level of Ijen Crater Tourism Resort by using its natural resources, uniqueness, and capability. Its natural resources and uniqueness, which are the core competencies, must be well maintained as the strongest factors to attract visitors; (5) Destination Management Organization (DMO) as a means of tourim resorts management is not yet applied in the management of Ijen Crater Tourism Resort. The application of the management system is expected to rise number of visitors and competition level of Ijen Crater Tourism Resort. The success of the application requires a good team work of related stakeholders in tourism industry.